Power system network sensitivity to voltage collapse - Althowibi, F. A. (IEEE, 2012)
Preventing voltage collapse occurrences in power systems are a challenging task worldwide. An adequate reactive power supply along with voltage limit violation may lead to blackout. The ability to sense such dynamic change and accurately determine voltage stability indications allows system control to take the necessary action to prevent such incidents. This paper presents efficient indices to calculate voltage stability analysis and predict system voltage collapse. Voltage stability margins can be calculated indicating how far the power system is from its severely loading condition. The proposed method was demonstrated on the 5-bus and IEEE 180-bus systems and compared with existing methods to show its validation and efficiency.